THE IMPACT OF ORGANIC FERTILIZER WITH EFFICIENT MICROORGANISMS ON SOIL QUALITY AND MAIZE PRODUCTIVITY - Mariana CARAMAN; Larisa CREMENEAC; Roman MOSCALIC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents the results of research on the impact of organic fertilizers, obtained from poultry manure with and without pro prebiotic PoultryStarRmeEU, on the microbiological and biochemical quality of soil and corn productivity. For this purpose, initially, an experiment was organized in the practical conditions of the individual poultry enterprise "GT Nicolaescu V." from village Fagureni, district Straseni, in which material for the study was used the probiotic PoultryStarRmeEU, and the object of research were broiler chickens ROSS 308. Subsequently, the manure obtained was subjected to traditional composting, and after 9 months, it was were injected into the soil. As a result of research, it was found that organic fertilizers have improved the microbiological and biochemical quality of the soil by increasing 10 times the amount of beneficial microorganisms, the content of organic matter - by 48.02% - 114.81% and humus - by 15.14% - 10.56%, thus stimulating the physiological development (height) of the plants by 7.69% - 10.53% and increasing the corn grain harvest by 5.98% and by 17.45% the amount of straw (organic matter) compared to the control group.